In vitro antifungal activity of trembesi leaf extract [Samanea saman (Jacq.) Merr.] against Colletotrichum magnum Rossman & Allen, the causal agent of papaya anthracnose - Ratnasari, Athalia; Darmadi, Anak Agung Ketut; Inabuy, Fainmarinat selviani; Sudatri, Ni Wayan (Universitas Lampung, 2025)
Papaya fruit production in Bali has decreased over the last three years (2020-2022). One of the contributing factors is infection by Colletotrichum spp., which causes anthracnose. Anthracnose is an airborne disease that infects various plant commodities including papaya. The use of chemical fungicides to control anthracnose can have negative impacts if used long-term. Trembesi [Samanea saman (Jacq.) Merr.] extract has previously been reported to possess antifungal, antiseptic, antibacterial, and antidiabetic properties. This study aimed to determine the effectiveness and category of inhibitory activity, Minimum Inhibitory Concentration (MIC), Lethal Concentration 50% (LC??), and the phytochemical content of trembesi leaves. Methanol extract of trembesi leaves effectively inhibited the growth of Colletotrichum magnum at a concentration of 5%. The experiment used 11 treatments with 4 replications, including control (0% v/v) and extract concentrations of 1% to 10% (v/v), along with a positive control. The corresponding inhibition zone diameters were: 0.00 mm, 12.00 mm, 11.87 mm, 13.62 mm, 16.00 mm, 19.62 mm, 15.75 mm, 16.87 mm, 17.87 mm, 17.87 mm, 18.25 mm, and 20.87 mm, respectively. The minimum concentration of extract showing inhibitory activity (MIC) was 0.3%, while the LC?? value was 0.32%. Phytochemical screening revealed the presence of phenolics, tannins, alkaloids, steroids, terpenoids, flavonoids, and saponins in the trembesi leaf extract.